Influence of Innate Immunity on Cancer Cell Stemness - Pastò, Anna (Int J Mol Sci, 2020)
Even if cancer stem cells (CSCs) represent only a small proportion of the tumor mass, they significantly account for tumor maintenance, resistance to therapies, relapse and metastatic spread, due to their increased capacity of self-renewal, multipotency, tumorigenicity and quiescence. Emerging evidence suggests that the immune contexture within the tumor microenvironment (TME) determines both the response to therapy and the clinical outcome. In this context, CSCs acquire immune evasion skills by editing immune cell functions and sculpting the immunosuppressive landscape of TME. Reciprocally, infiltrating immune cells influence CSCs self-renewal, tumorigenicity and metastasis. In this review, we summarize the immunomodulatory properties of CSCs, as well as the impact of innate immune cells on cancer cells stemness in the different phases of cancer immunoediting process and neoplastic progression.